Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1371/journal.pone.0044819
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of HIV Infection among Men Who Have Sex with Men in Switzerland: Mathematical Modelling Study

Abstract: BackgroundNew HIV infections in men who have sex with men (MSM) have increased in Switzerland since 2000 despite combination antiretroviral therapy (cART). The objectives of this mathematical modelling study were: to describe the dynamics of the HIV epidemic in MSM in Switzerland using national data; to explore the effects of hypothetical prevention scenarios; and to conduct a multivariate sensitivity analysis.Methodology/Principal FindingsThe model describes HIV transmission, progression and the effects of cA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 28 publications
(21 reference statements)
5
44
1
Order By: Relevance
“…Despite earlier concerns about an increase in heterosexual cases and “feminization” of the epidemic, the findings of this study indicate a predominance of new infections among MSM, corroborating evidence of a resurgence of the epidemic in this population group in other countries 3 , 23 . A research conducted incidence 10 Brazilian cities, using Respondent Driven Sampling as sampling method, showed prevalence of HIV of 14.2% among MSM 11 , approximately 30 times greater than the prevalence of HIV in the heterosexual male population.…”
Section: Discussionsupporting
confidence: 77%
“…Despite earlier concerns about an increase in heterosexual cases and “feminization” of the epidemic, the findings of this study indicate a predominance of new infections among MSM, corroborating evidence of a resurgence of the epidemic in this population group in other countries 3 , 23 . A research conducted incidence 10 Brazilian cities, using Respondent Driven Sampling as sampling method, showed prevalence of HIV of 14.2% among MSM 11 , approximately 30 times greater than the prevalence of HIV in the heterosexual male population.…”
Section: Discussionsupporting
confidence: 77%
“…This represents the only such study in Latin America, though the data from different international settings provide variable findings. For example, a recent modeling study in Switzerland showed that 81.8% of new infections were attributable to HIV-infected MSM who were unaware of their status (24), underscoring the public health consequences of ensuring that MSM are regularly screened and aware. Recent studies among MSM in Paris and Melbourne, similarly recruited using convenience sampling, showed that only 19.7% and 31.1%, respectively, of those who were HIV-infected were unaware of their status (25, 26), indicating a vast difference between these samples from high-income countries and ours in a middleincome setting.…”
Section: Discussionmentioning
confidence: 99%
“…Viral phylogenetic studies have proved especially critical in evaluating the early impact of treatment as prevention programs in Europe, which has experienced a recent resurgence of HIV infection among MSM (36, 37). A phylogenetic analysis of the Dutch HIV epidemic using data from the ATHENA observational HIV cohort study evaluated sources of HIV transmission among recently infected MSM (7).…”
Section: Integrating Hiv Phylogenetics To Understand Characteristics mentioning
confidence: 99%